Microvascular imaging versus CEUS in the characterization of renal masses: preliminary experience in a tertiary care referral university hospital - Bertelli, Elena; Vizzi, Michele; Lattavo, Lorenzo; Ruzga, Ron; Giovannelli, Simona; Cozzi, Diletta; Valeri, Federico; Agostini, Simone; Miele, Vittorio (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Evaluation of the possible role of microvascular imaging (MI) for the detection of vascularization of renal lesions, while comparing it with contrast-enhanced ultrasound (CEUS).137 patients (160 renal lesions, 64 solid and 96 cystic) were enrolled in this single-center, retrospective, observational study. For solid masses, both the intralesional and the peripheral vascularization was analyzed and quantified by MI and then compared to peak enhancement on CEUS. Regarding cystic lesions, we evaluated the presence or absence of vascularization within the cystic wall and/or septa. MI results were compared with CEUS findings using Pearson’s Chi square test. An optimal size cut-off for renal lesions was determined with the Youden test.For solid lesions, a statistically significant correlation (p <0.05) was observed between the MI parameters and the peak enhancement on CEUS. The detection rate (DR) for lesional vascularization on MI was 87.5%, while if we consider only lesions larger than the optimal cut-off (14mm), the DR increases to 98%. In cystic lesions, the MI showed a high specificity (93.9%) in predicting CEUS results and a high positive predictive value (84.2%). The concordance was 100% in Bosniak I lesions and 80% in Bosniak IV lesions, while it was lower for the other classes. Furthermore, we found a statistically significant correlation (p <0.05) between Bosniak grade and lesional vascularity on MI.Our preliminary study shows that MI cannot replace CEUS, but could reduce its use, especially in solid lesions larger than 14mm and in cysts classified as Bosniak IV, a goal that is particularly important in an active surveillance setting.
Keywords: Urinary tract; renal lesions; microvascular imaging; CEUS; renal cysts